Regulation of Transit Issues: Multilateral International Treaties and National Law - Sarsembayev, Marat Aldangorovich; Sarsembayev, Daniyar Maratovich; Lazzat Talgatovna Nazarkulova, Aiman Kudaibergenovna Kussainova, (Opción, 2019)
This article discusses the theoretical and practical foundations of international violation of national and international legal norms for the transit of goods, cargo, and passengers via comparative qualitative research methods. The practical and theoretical significance of the research results consists in putting forward proposals to improve the norms of international conventions and Kazakhstani legislation on transit issues, and to deepen the scientific analysis of domestic and international aspects of transport transit. In conclusion, analysis of the texts of international treaties on transit issues showed that they do not settle transit issues systematically.